Experimental study of the 13C+12C fusion reaction at deep sub-barrier energies. (April 2016) - Tudor, D.; Chilug, A.I.; Straticiuc, M.; Trache, L.; Chesneanu, D.; Toma, S.; Ghita, D. G.; Burducea, I.; Margineanu, R.; Pantelica, A.; Gomoiu, C.; Zhang, N.T.; et al.
Abstract: Heavy-ion fusion reactions between light nuclei such as carbon and oxygen isotopes have been studied because of their significance for a wide variety of stellar burning scenarios. One important stellar reaction is 12 C+ 12 C, but it is difficult to measure it in the Gamow window because of very low cross sections and several resonances occurring. Hints can be obtained from the study of 13 C+ 12 C reaction. We have measured this process by an activation method for energies down to Ecm =2.5 MeV using 13 C beams from the Bucharest 3 MV tandetron and gamma-ray deactivation measurements in our low and ultralow background laboratories, the latter located in a salt mine about 100 km north of Bucharest. Results obtained so far are shown and discussed in connection with the possibility to go even further down in energy and with the interpretation of the reaction mechanism at such deep sub-barrier energies.